Behavior of severe maxillofacial trauma - Denia Morales Navarro; Yassim Aguila Nogueira; Ileana Bárbara Grau León (Editorial Ciencias Médicas, 2018)
Introduction: Understanding the cause, severity and distribution of facial trauma and concomitant lesions may help in the optimization of initial treatment. Objective: To characterize severe maxillofacial trauma in the emergency department of General Calixto García University Hospital from 2015-2016. Methods: A descriptive and cross-sectional study was carried out at General Calixto García University Hospital, from 2015-2016. The study population was constituted by patients who presented to the emergency department with a diagnosis of maxillofacial polytrauma and severe maxillofacial trauma. We used the following qualitative variables: sex, etiology, drinking of alcohol and lesions. We used the quantitative variable of age. A data collection form was prepared and the information was entered into a database. Whole numbers, percentages and statistical tables were used. Ethical principles for human research were followed. Results: Males accounted for 73 %. The most represented age group was 18-30 years (32.4 %), followed by the 31-40 and 41-50 groups (21.6 % and 14.9 %, respectively). In 44.6 % of the patients the trauma was associated to traffic accidents. In 32.4% of the patients, the trauma was associated to interpersonal violence. Ethyl breath was detected in 50 % of the patients. Predominating wounds were larger than 2 cm, followed by those of less than that length (52.7 % and 28.4 %, respectively) and mandibular fracture (29.7 %). Conclusions: There was a predominance of males and the age group of 18-30 years. The main etiology was traffic accident, followed by interpersonal violence. The most frequent soft-tissue lesions were wounds greater than 2 cm. The most frequent hard-tissue lesions were mandibular fractures. Half of the patients had consumed alcohol.